2021
DOI: 10.3390/ijms22062948
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Extracellular ATP by Vascular Smooth Muscle Cells Transdifferentiated into Chondrocytes Generates Pi but Not PPi

Abstract: (1) Background: Tissue non-specific alkaline phosphatase (TNAP) is suspected to induce atherosclerosis plaque calcification. TNAP, during physiological mineralization, hydrolyzes the mineralization inhibitor inorganic pyrophosphate (PPi). Since atherosclerosis plaques are characterized by the presence of necrotic cells that probably release supraphysiological concentrations of ATP, we explored whether this extracellular adenosine triphosphate (ATP) is hydrolyzed into the mineralization inhibitor PPi or the min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In a subsequent study, the authors explored the use of two‐dimensional correlation IR spectroscopy to resolve band overlap [74] . More recently, IR spectroscopy was employed in combination with 31 P NMR spectroscopy to monitor extracellular TNAP and other ectonucleoside triphoshatediphosphohydrolase sequential conversion of ATP to ADP and P i , then to AMP and P i , and finally adenosine and P i , without the formation of PP i during this process [75] . Overall, infrared spectroscopy provides time‐dependent spectra by which one can follow enzyme kinetics.…”
Section: Detection Methodsmentioning
confidence: 99%
“…In a subsequent study, the authors explored the use of two‐dimensional correlation IR spectroscopy to resolve band overlap [74] . More recently, IR spectroscopy was employed in combination with 31 P NMR spectroscopy to monitor extracellular TNAP and other ectonucleoside triphoshatediphosphohydrolase sequential conversion of ATP to ADP and P i , then to AMP and P i , and finally adenosine and P i , without the formation of PP i during this process [75] . Overall, infrared spectroscopy provides time‐dependent spectra by which one can follow enzyme kinetics.…”
Section: Detection Methodsmentioning
confidence: 99%
“…It is surprising as one might have expected some anti-calcification activity as it competes with ENPP1 for ATP usage, and could possibly have had some influence on PPi production, which seems to depend on the ratio of ENPP1 to ENTPD1 activity [210]. Remarkably, it has recently been shown that hydrolysis of extracellular ATP by VSMCs undergoing chondrocyte-like differentiation generates Pi but not PPi [211], suggesting the loss of pyrophosphate generation and/or an increase in NTPDase activity. While ENPP1 exerts a clear anti-calcifying activity, the role of CD39 in SMC calcification is not obvious and could depend on circumstances.…”
Section: Vascular Smooth Muscle and Endothelial Cells-cd39mentioning
confidence: 99%
“…Interestingly, Tnap −/− mice still have small crystals that fail to grow, suggesting that TNAP may play a role in modulating crystal growth [47]. Recently, Buchet and colleagues found that TNAP in VSMCs also hydrolyzes exogenous ATP in a sequential manner to yield Pi, leading them to posit that TNAP may directly contribute to calcification by generating the phosphate component of the mineral [50]. However, for this to occur, extracellular ATP concentration would need to be in millimolar concentration, which does occur in the tumor microenvironment [51] and conceivably could occur in the atherosclerotic milieu as well.…”
Section: Activator Biomolecules 61 Tnapmentioning
confidence: 99%